Maritime Diplomacy of the Indonesian Navy on Sail Australia 1998 - Anindito, Royan Hanung (Diponegoro University, 2022)
In the 90s, Indonesia's relations with Australia often had ups and downs. In addition, Australia has been a neighbour of Indonesia for a long time. Thus, Indonesia conducts Maritime Diplomacy so as not to cause more significant turmoil. Australia celebrated Australia Day 1998 by inviting Tall Ships from various countries. Indonesia was invited to visit the Royal Australian Navy (RAN), so Indonesia was willing to join the Sail Australia 1998 event. Indonesia joined Sail Australia in 1998. The cruise was adjusted to the AAL schedule to carry out Kartika Jala Krida. Therefore, the voyage was named Kartika Jala Krida 1998 to Sail Australia. During the voyage, KJK ‘98 experienced several dynamics. The tail of KRI Dewaruci was hit by a storm when the race did not get wind. When one of the KJK ‘98 was going to visit the Indonesian Ambassador in Canbera on the roadside, there were several demos about Timor-Timor. Thus, no matter the circumstances, Indonesian sailors, through the KJK ‘98 team, still show as professional, trengginas, tanggon, and responsive sailors. KJK ‘98 shows the performance of the AAL cadet marching band, ship parade, sailing role, and traditional dance using traditional customs. Open Ship also introduces Indonesian culture. The results of the struggle of Indonesian sailors fascinated the Australian people, who were amazed by Indonesia and then KJK ‘98 received the most trophies. Thus, the results of maritime diplomacy can reduce friction between Indonesia and Australia. This research uses a maritime history approach that aims to keep the Indonesian generation in the maritime spirit even in the circumstances, regardless of conditions. First, why Indonesia carried out maritime diplomacy through participation in Sail Australia 1998, despite the monetary crisis. Second, what are the dynamics of the Navy's maritime diplomacy in participation in Sail Australia 1998. Third, how the public responds to Indonesia's maritime diplomacy towards Australia.